Aberrant activation of chromosome asynapsis checkpoint triggers oocyte elimination - Xiaofei Jiao; Zhongyang Liang; Jiwei Li; Long Bai; Jun Xu; Yidan Liu; Lin-Yu Lu (Nature Communications)
Abstract Chromosome synapsis is an evolutionarily conserved process essential for meiotic recombination. HORMAD1 and HORMAD2, which monitor chromosome asynapsis by localizing to unsynapsed chromosome axes, are removed from synapsed chromosome axes by TRIP13, though the biological significance of this process remains unclear. We show that when HORMAD1 and HORMAD2 are retained on synapsed chromosome axes, they recruit BRCA1, activate chromosome asynapsis checkpoint, and trigger oocyte elimination. Unexpectedly, N-terminal tagging retains HORMAD1 and HORMAD2 on synapsed chromosome axes without triggering oocyte elimination due to defective BRCA1 recruitment. Mechanistically, HORMAD1 co-immunoprecipitates with BRCA1 readily, not through the canonical closure motif-binding mode but via an interface on its HORMA domain near the N-terminus. HORMAD2 co-immunoprecipitates with BRCA1 weakly but also regulates its recruitment. Collectively, the TRIP13-dependent removal of HORMAD1 and HORMAD2 from synapsed chromosome axes is essential for female fertility, preventing aberrant chromosome asynapsis checkpoint activation and unintended oocyte elimination.